PETR BORKOVEC - THE POETS' GURU? - Cepicova, Vendula (Bohemica Olomucensia, 2022)
The study analyses the influence respected Czech poet Petr Borkovec (b. 1970) had on the younger Czech and Slovak poets being the editor of their poetry collections, namely Lom (2013) by Martina Blazekova, Ohen po slavnosti (2011) by Kamil Bouska, Snehy a dalsi (2010) by David Voda, Sut (2007) and Vlastiveda (2010) by Jonas Hajek, and Co drzi Nizozemi (2010) by Viktor Spacek. They and Borkovec share many common features of their respective poetics, such as lyrical description of the countryside and abandoned houses, observational distance, refined formal qualities of the poems, or the change of state as a main theme.
Keywords: Petr Borkovec; Czech poetry; lyrical description; observational distance; authenticity